Women Employee Rights in Garment Industry, Tirupur - Thangaraj, Nathiya; Subramaniyam, Parthiban; Rangasamy, Shanthi (International Journal of Social Sciences and Management, 2016)
Women are playing a vital role in earning even net national product of the country through their income. This study is undertaken to study about how the women are utilizing their rights properly especially in garment industry. The reason to choose the industry is that the women participation in the industry is 70,000 especially in Tirupur. This research is undertaken to analyze about the women’s rights in garment industry in the area of Tirupur. This study is undertaken to make an analysis of how women are working in their working area and also regarding the facilities provided in the working environment such as crèche facilities, ventilation facilities and payment benefits, work enrichment opportunities. The prime objective of the present study is to evaluate the Women Employee Rights in garment industry in Tirupur. The study was conducted on the basis of descriptive research. The employees have been selected by using non-probability convenience sample method from various departments. Totally 200 sample respondents were selected and analysed using t-Test, Chi-Square test and Garrett’s ranking method. Int. J. Soc. Sci. Manage. Vol-3, issue-2: 119-124